1984
DOI: 10.3109/00016488409107534
|View full text |Cite
|
Sign up to set email alerts
|

Increased Capillary Permeability of the Stria Vascularis to HRP, Induced by Experimental Acute Hypotension in Rats

Abstract: Acute hypotension was produced in rats by using two experimental techniques: intravenous infusion of a ganglion-blocking agent (Arfonad), and venesection of a femoral vein. Horseradish peroxidase (HRP) was injected intravenously after each procedure, and subsequently observed in the inner ear by light and electron microscopy. In both experimental models, a large amount of tracer spread into the intercellular spaces, but it was halted by tight junctions bordering the stria vascularis. The endothelium exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This may support the notion that FA mitigates structural changes but has marginal effect on hearing. Gratton and Schulte (1995), Johnsson and Hawkins (1972), Sakagami et al (1984) and Ohlemiller et al (2008) reported alterations in microvasculature associated with atrophy of the stria vascularis in quitaged gerbils. Further, the cochlea has a rich vascular supply, which is embedded in double layer bed of epithelium, where the arterial supply breaks into minute capillaries (Gopinath et al, 2010).…”
Section: Hearing Researchmentioning
confidence: 95%
“…This may support the notion that FA mitigates structural changes but has marginal effect on hearing. Gratton and Schulte (1995), Johnsson and Hawkins (1972), Sakagami et al (1984) and Ohlemiller et al (2008) reported alterations in microvasculature associated with atrophy of the stria vascularis in quitaged gerbils. Further, the cochlea has a rich vascular supply, which is embedded in double layer bed of epithelium, where the arterial supply breaks into minute capillaries (Gopinath et al, 2010).…”
Section: Hearing Researchmentioning
confidence: 95%